Manipulating the Shape of Flexible Magnetic Nanodisks with Meronlike Magnetic States - Elias-Moreno, R (American Physical Society, 2022)
The control of the magnetic properties of shapeable devices and the manipulation of flexible structures by external magnetic fields is a keystone of future magnetoelectronics-based devices. In this work we study the elastic properties of a flexible magnetic nanodisk that hosts a meron as the magnetic state and can be deformed from structures with positive to negative Gaussian curvature. We show that the winding number of the hosted meron is crucial to determine the curvature sign of the stable obtained shape. Additionally, we show that the curvature that minimizes the total energy of the nanodisk depends on geometrical and mechanical parameters. It is shown that an increase in the external radius and Young s modulus leads to a decrease in the curvature absolute value. Finally, it is shown that the nanodisk s shape also depends on the connection between the polarity and chirality of the meronlike state. © 2022 American Physical Society.